Alterations in Lipid Mediated Signaling and Wnt/β-Catenin Signaling in DMH Induced Colon Cancer on Supplementation of Fish Oil. (5th June 2014) - Kansal, Shevali; Vaiphei, Kim; Agnihotri, Navneet
Abstract : Ceramide mediates inhibition of cyclooxygenase-2 (COX-2) which catalyzes formation of prostaglandin further activating peroxisome proliferator-activated receptor γ (PPAR γ ) and Wnt/ β -catenin pathway; and hence plays a critical role in cancer. Therefore, in current study, ceramide, COX-2, 15-deoxy prostaglandin J2 (15-deoxy PGJ2 ), PPAR γ, and β -catenin were estimated to evaluate the effect of fish oil on lipid mediated and Wnt/ β -catenin signaling in colon carcinoma. Male Wistar rats in Group I received purified diet while Groups II and III received modified diet supplemented with FO : CO(1 : 1) and FO : CO(2.5 : 1), respectively. These were further subdivided into controls receiving ethylenediaminetetraacetic acid and treated groups receiving dimethylhydrazine dihydrochloride (DMH)/week for 4 weeks. Animals sacrificed 48 hours after last injection constituted initiation phase and those sacrificed after 16 weeks constituted postinitiation phase. Decreased ceramide and increased PPAR γ were observed in postinitiation phase only. On receiving FO+CO(1 : 1)+DMH and FO+CO(2.5 : 1)+DMH in both phases, ceramide was augmented whereas COX-2, 15-deoxy PGJ2, and nuclear translocation of β -catenin were reduced with respect to cancerous animals. Decrease was more significant in postinitiation phase with FO+CO(2.5 : 1)+DMH. Treatment with oils increased PPAR γ in initiation phase but decreased it in postinitiation phase. Hence, fish oil altered lipid mediated signalling in a dose and time dependent manner so as to inhibit progression of colon cancer.